2013
DOI: 10.1016/j.immuni.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Monocytes Recruited to Allergic Skin Acquire an Anti-inflammatory M2 Phenotype via Basophil-Derived Interleukin-4

Abstract: Monocytes and macrophages are important effectors and regulators of inflammation, and both can be divided into distinct subsets based on their phenotypes. The developmental and functional relationship between individual subsets of monocytes and those of macrophages has not been fully elucidated, although Ly6C(+)CCR2(+) inflammatory and Ly6C(-)CCR2(-) resident monocytes are generally thought to differentiate into M1 (classically activated) and M2 (alternatively activated) macrophages, respectively. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(220 citation statements)
references
References 65 publications
11
208
1
Order By: Relevance
“…In addition, release of IL-4 and IL-13 by basophils may induce alternatively activated macrophages, which in turn play a role in tissue homeostasis and repair [40,41]. Therefore, synergy in cytokine production by basophils may amplify Th2-type immune responses via T cell-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, release of IL-4 and IL-13 by basophils may induce alternatively activated macrophages, which in turn play a role in tissue homeostasis and repair [40,41]. Therefore, synergy in cytokine production by basophils may amplify Th2-type immune responses via T cell-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years several genetic mouse models have been used to elucidate basophil functions in vivo. It has been shown that basophils cooperate with dendritic cells to initiate Th2 responses, promote alternative activation of macrophages, and contribute to acquired resistance against parasites (12)(13)(14)(15)(16). We and others have shown that basophils contribute to protective immune responses against secondary infection by Nb and ticks (13,14,17).…”
mentioning
confidence: 85%
“…On the other hand, an unexpected interaction between basophils and monocytes-macrophages was observed during allergic skin inflammation [22]. The fate, polarization and function of monocytes after their recruitment to skin lesions were analyzed under an immunoglobulin Emediated chronic allergic inflammation (IgE-CAI), a model where basophils play a critical role.…”
Section: Basophils and Th2 Cell Responsesmentioning
confidence: 99%